SISTEM PENDUKUNG KEPUTUSAN SELEKSI SUPPLIER BAHAN BAKU DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - oke hariansyah (KERNEL: Jurnal Riset Inovasi Bidang Informatika dan Pendidikan Informatika, 2020)
Selection of suppliers for the company or the industry needs to be done to get the supplier truly able to meet the company's needs consistently. In this study, will be appointed a case of finding the best alternative based on the criteria that have been determined using the Fuzzy Multiple Attribute Decision Making (FMADM) Simple Additive Weighting method (SAW). This method was chosen because it is able to select the best alternative from a number of alternatives, in this case the alternative is intended to determine the best supplier based on specified criteria. Based on test results, the application of the system to be implemented to help the work of doing the selection of purchasing parts supplier, can speed up the process of selecting suppliers, and can facilitate the purchasing section chief part in determining the proper supplier selection, proper and appropriate